Availability, procurement, training, usage, maintenance and complications of electrosurgical units and laparoscopic equipment in 12 African countries. Issue 2 (27th January 2020) - Oosting, R. M.; Wauben, L. S. G. L.; Madete, J. K.; Groen, R. S.; Dankelman, J.
Abstract : Background: Strategies are needed to increase the availability of surgical equipment in low‐ and middle‐income countries (LMICs). This study was undertaken to explore the current availability, procurement, training, usage, maintenance and complications encountered during use of electrosurgical units (ESUs) and laparoscopic equipment. Methods: A survey was conducted among surgeons attending the annual meeting of the College of Surgeons of East, Central and Southern Africa (COSECSA) in December 2017 and the annual meeting of the Surgical Society of Kenya (SSK) in March 2018. Biomedical equipment technicians (BMETs) were surveyed and maintenance records collected in Kenya between February and March 2018. Results: Among 80 participants, there were 59 surgeons from 12 African countries and 21 BMETs from Kenya. Thirty‐six maintenance records were collected. ESUs were available for all COSECSA and SSK surgeons, but only 49 per cent (29 of 59) had access to working laparoscopic equipment. Reuse of disposable ESU accessories and difficulties obtaining carbon dioxide were identified. More than three‐quarters of surgeons (79 per cent) indicated that maintenance of ESUs was available, but only 59 per cent (16 of 27) confirmed maintenance of laparoscopic equipment at their centre. Conclusion: Despite the availability of surgical equipment, significant gaps in access to maintenance were apparent in these LMICs, limiting implementation of open and laparoscopic surgery. Abstract : This study investigated the current availability, procurement, training, usage, maintenance and complications in low‐ and middle‐income countries (LMICs) of two types of surgical equipment: the electrosurgical unit and laparoscopic equipment. Despite the availability of surgical equipment, surgeons still encountered complications during use of both types of surgical equipment. Reducing gaps in the availability of training and access to maintenance, together with the implementation of equipment that fits current use in LMICs, are important steps in reaching global implementation of open and laparoscopic surgery. Adoption of new technology is complex Abstract : Antecedentes: En países de bajos y medianos ingresos ( low‐ and middle‐income countries, LMIC) hay que desarrollar estrategias de futuro para incrementar la disponibilidad de equipos quirúrgicos, adquisición, capacitación, uso, mantenimiento y complicaciones relacionadas con las unidades electroquirúrgicas ( electrosurgical unit, ESU) y los equipos de laparoscopia. Métodos: Se realizó una encuesta entre los cirujanos que asistieron a la reunión anual del Colegio de Cirujanos de África Oriental, Central y Meridional ( College Of Surgeons of East, Central and Southern Africa, COSECSA) en diciembre de 2017 y a la reunión anual de la Sociedad Quirúrgica de Kenia ( Surgical Society of Kenya, SSK) en marzo de 2018. Se encuestaron también a los técnicos de equipos biomédicos ( Biomedical Equipment Technicians, BMET) y se recopilaron los registros de mantenimiento en Kenia entre febrero y marzo de 2018. Resultados: Participaron 80 sujetos, 59 cirujanos de 11 países africanos y 21 BMET de Kenia. Se recopilaron 36 registros de mantenimiento. Todos los cirujanos de COSECSA y SSK disponían de ESU, pero menos de la mitad (49%) disponían de equipos de laparoscopia. Como principales problemas se detectaron la reutilización de accesorios desechables en las ESU y las dificultades para disponer de CO2. Más de las tres cuartas partes (78%) de los cirujanos contaban con equipos de mantenimiento para las ESU, pero solo el 59% disponía de mantenimiento para los equipos de laparoscopia en su centro. Conclusión: A pesar de la disponibilidad de equipos quirúrgicos, en estos LMIC se detectaron serias dificultades en su mantenimiento, hecho que limita la implementación de la cirugía abierta y laparoscópica.